The Effect of Public Information and Competition on Trading Volume and Price Volatility - Foster, F. Douglas; Viswanathan, S. (Review of Financial Studies, 1993)
In a one-period model of market making with many exogenously informed traders, we first show that the variance of prices and expected trading volume depend on the public information released at the start of trading. This is accomplished by representing beliefs with elliptically contoured distributions, for which the form of optimal decision rules does not depend on the specific distribution used. Second, if the model is altered so that the decision to become informed is made endogenous, then the decision rules of the market-maker and informed traders depend on the public information. Third, in a multiperiod model with many informed traders and long-lived private information, recursion formulas similar to those of Kyle (1985) hold for all elliptically contoured distributions, trading volume is autocorrelated and, unless per period liquidity trading is bounded away from zero as new trading periods are added, informed traders’ profits vanish.